The Distributed Image - Rothöhler, Simon (Brill, 2024)
The ubiquity of digital images is an effect of their distributive versatility. They can be stored almost indefinitely, transmitted instantaneously, reproduced without any effort, visualized in many ways, datafied and processed. Their mobilization does not take place randomly, but follows a complex media logistics of format standards, infrastructures and transport calculations. Digital images are distributed: not as sessile objects, fixed entities, but as stream-like modulated processes. The study conceptualizes actors and agendas of image data traffic, examines retro-digitized archive image corpora with regard to their distribution histories, and deals with ‹calmed› image sensor operations in intelligent environments.